Immigration Policy, Assimilation of Immigrants and Natives' Sentiments towards Immigrants: Evidence from 12 OECD-Countries - Thomas K. Bauer; Magnus Lofstrom; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2000)
As in the U.S. and Canada, migration is a controversial issue in Europe. This paper explores the possibility that immigration policy may affect the labor market assimilation of immigrants and hence natives? sentiments towards immigrants. It first reviews the assimilation literature in economics and the policy approaches taken in Europe and among the traditional immigration countries. Second, a new analysis of individual data from the OECD countries studies sentiments concerning immigration and the determinants of these sentiments is presented. Natives in countries that receive predominantly refugee migrants are relatively more concerned with immigrations impact on social issues such as crime than on the employment effects. Natives in countries with mostly economic migrants are relatively more concerned about loosing jobs to immigrants. However, the results also suggest that natives may view immigration more favorably if immigrants are selected according to the needs of the labor markets. Possible benefits of such a policy are that it may moderate social tensions in regards to migration and contribute to a better economic performance of the respective countries.
Keywords: F22; J61; 330; Assimilation of migrants; European migration policies; sentiments towards migrants; Migrationspolitik; Soziale Integration; Migranten; Öffentliche Meinung; Flüchtlinge; Soziales Problem; Ausländische Arbeitskräfte; Arbeitslosigkeit; Schätzung; OECD-Staaten